Combined effects of ocean acidification and nutrient levels on the photosynthetic performance of Thalassiosira (Conticribra) weissflogii (Bacillariophyta). Issue 2 (1st March 2018) - Yang, Yuling; Li, Wei; Li, Zhenzhen; Xu, Juntian
Abstract: The purpose of this study was to investigate the effects of ocean acidification and nutrient level on the growth and photosynthetic performance of the diatom Thalassiosira ( Conticribra ) weissflogii . Cells were exposed to varying levels of CO2 [current CO2 (LC), 400 μatm; high CO2 (HC), 1000 μatm] and nutrients, with NO3 − and PO4 3− concentrations enriched, respectively, at 50 μmol l −1 and 5 μmol l −1 [high nutrient (HN)], 20 μmol l −1 and 2 μmol l −1 [mid-level nutrient (MN)] and 10 μmol l −1 and 1 μmol l −1 [low nutrient (LN)]. After acclimatization for over 20 generations, no significant differences in growth rates were observed between LC and HC cultures under both HN and LN conditions; whereas, HC significantly reduced the growth rate under MN conditions. Lower nutrient loading significantly inhibited the growth rates of both LC and HC cultures; whereas, HC (but not LC) significantly decreased chlorophyll a and carotenoid contents in LN treatments. HC conditions significantly increased maximum relative electron transport rates (rETRmax ) and saturating light intensity (Ik ) of HN cultures, with rETRmax showing a positive relationship with growth rates stimulated by nutrient enrichments. The maximum ( F v / F m ) and effective quantum yield (Yield) were all inhibited under LN conditions, with the greatest reduction in Yield observed under LC conditions, corresponding to the highest nonphotochemical quenching, lowest light use efficiency (α) and lowest rETRmax . Based on these results, ocean acidification and nutrient availability may influence photosynthetic performance in T. weissflogii individually or interactively, with the future growth of marine diatoms mediated by these codependent environmental drivers.